Artificial intelligence in EFL Higher Education: A qualitative study of opportunities, challenges, and pedagogical implications - Nurul Anam; Shovi Yatul Istifadah (Indonesian Journal of Learning and Educational Studies, 2026)
The accelerating development of artificial intelligence (AI) has increasingly reshaped English as a Foreign Language (EFL) pedagogy, particularly in supporting language learning and linguistic development in higher education contexts. This study aims to critically examine the opportunities, challenges, and pedagogical implications of AI integration, with a specific emphasis on language skills development, particularly writing and speaking. Employing a qualitative research design, data were collected through in-depth interviews, classroom observations, and document analysis involving English lecturers and EFL students. The data were analyzed using thematic analysis to identify recurring patterns and experiences related to AI-supported language learning. The findings indicate that AI significantly enhances language learning by supporting the development of writing accuracy, grammatical control, and speaking fluency through immediate and adaptive feedback. AI also promotes learner autonomy and increases engagement in language production activities, enabling students to practice language skills beyond classroom constraints. However, challenges were identified, including students’ overreliance on AI-generated outputs and limited deep processing of linguistic forms. This study contributes to the growing body of research on AI in English language education by providing qualitative insights into how AI supports language learning processes and language skills development. The findings offer practical implications for designing pedagogically grounded AI-assisted language learning environments.